Housing Stability & Social Capital: A Mixed-Method Analysis of the Relationship Between Housing Stability, Psychological Integration, and Social Capital Among Individuals with Histories of Homelessness - Agha, Ayda (Université d'Ottawa / University of Ottawa, 2024)
Social capital, which encompasses the resources and benefits derived from social networks and community participation, is crucial in improving well-being and societal inclusion. This dissertation examines the relationship between housing stability and social capital among individuals with histories of homelessness, exploring the influence of social support and psychological integration as mediating variables on this relationship. The research comprises two complementary studies: a quantitative observational longitudinal study that examines housing stability over time, and a qualitative study delving into personal narratives of housing and community experiences. Study one investigates if housing stability predicts social capital, specifically trust and linking social capital, in a sample of 900 homeless and vulnerably housed individuals living in three Canadian cities. Using path analysis, findings reveal that while housing stability is not directly associated with social capital, higher levels of social support and psychological integration mediate this relationship. These results underscore the importance of social support networks and a sense of community belonging to build social capital for those transitioning from homelessness. Study two explores the narratives of 30 individuals with low and high housing stability through qualitative analysis, focusing on their experiences with social relationships, the communities in which they reside, and interactions with service providers and government institutions. The findings highlight the critical role of family, friends, and community members in providing emotional and instrumental support essential for bonding and bridging social capital. However, challenges such as social isolation, interpersonal conflicts, and substance use are identified as significant barriers to creating social capital. Experiences with service providers and government organizations are explored, with individual service providers often making substantial positive impacts, while systemic issues remain problematic. Overall, this research contributes to the literature on housing instability by demonstrating the pivotal role of social support and psychological integration in fostering social capital, thereby improving the well-being and societal participation of individuals with histories of homelessness. The insights gained from this work highlight the necessity for holistic approaches in addressing homelessness, emphasizing the relationship between stable housing and social capital as being fundamental to achieving social inclusion in communities.
Keywords: Homelessness; Housing Stability; Social Capital